Diseño de un sistema de tratamiento de agua de producción del Campo Rubiales para disposición en riego (2021)
In this research project, a proposal is developed for the current CPF-2 treatment system in the Rubiales field. Whose purpose is to obtain treated production water, which meets the quality parameters established in Resolution 1207 of 2014 for use in agricultural activity. For the selection of the polishing treatment alternative, an AHP multi-criteria decision matrix is ​​carried out which evaluates the alternatives with respect to technical, economic, environmental and social criteria, additionally a subjective component is considered given by a group of experts and a robust bibliographic review, obtaining reverse osmosis as the most favorable option. Subsequently, a stationary quantitative simulation is performed that seeks to validate the current treatment system and design a proposal for the reverse osmosis unit. The results obtained at the exit of the reverse osmosis present a composition of optimum quality for the disposal of water in irrigation. Finally, an evaluation of the annual cost of the reverse osmosis system is carried out considering the cost of investment in equipment, labor and energy cost.